(untitled) (International Journal of Physiotherapy, 2020)
Background: Physical activity has been identified as a significant adjuvant in improving quality of life and lowering the cost of medicine. A positive effect has been seen on the mental and physical health of an individual influenced by physical activity and sleep. There is a scarcity of studies that determined the correlation between sleep patterns and physical activity among sports players. The present study is aimed to assess the association between physical activity and sleep among sports players. Methods: The present study was carried in Faridabad with a sample size of 133 sports players with age criteria between 18-25 years. The subjects were runners, shooters, and archers. WHO Questionnaire for physical activity was used to assess the physical activity of sports players. The Sleep Pattern was evaluated by using the “Pittsburgh Sleep Quality Index.” Results: The study results revealed that all of the runners (100%) were having vigorous activity. 72.7% of archers had moderate activity, but 58.8% of shooters had sedentary activity. Most of the sports payers were having a fairly good quality of Sleep (P=0.65). No correlation was observed between the Global Physical Activity Questionnaire Score of the subjects with any Sleep Domain. Conclusion: The study concluded that among different sports players doing sedentary, moderate, or heavy physical activity were having good quality sleep. This means even a small amount of physical activity can contribute to good quality sleep.